University faculty perceptions of training transfer and professional growth: a qualitative study - Gautam, Anju; Dahal, Niroj; Hasan, Md. Kamrul (Frontiers in Education, 2025)
University faculty recognize training transfer as significant for professional development, enhancing skills/knowledge, building confidence, fostering career growth, promoting collaboration, and benefiting institutions. This qualitative study, grounded in constructivist learning theory, experiential learning theory, and situated learning theory, explores faculty perceptions of research methods training transfer in their context. Conducted at Kathmandu University School of Education, Lalitpur, Nepal, in March 2024, the study utilized semi-structured interviews across three phases (initial, follow-up, and final) with five purposefully selected faculty members (three male and two female) participating in professional development programs. Thematic analysis identified four key themes as barriers: (1) training initiatives lacking systematic needs assessments, (2) an overreliance on lecture-based delivery with minimal hands-on application, (3) contextual challenges in skill implementation due to time constraints and resource limitations, and (4) the absence of institutional follow-up mechanisms to evaluate training impact or address emerging needs. Findings underline a disconnect between faculty expectations and institutional training frameworks in research methodology training. However, professional development programs are essential for adapting to academic demands. So, the study highlights the need for context-sensitive, differentiated training approaches that directly align with faculty expertise levels and workplace realities. Recommendations include implementing participatory needs assessments, adopting active learning pedagogies (e.g., peer collaboration, real-world data workshops), securing institutional resources for sustained practice, and establishing structured post-training evaluations. This study contributes to the global discourse on faculty development by emphasizing the collaboration between situated learning environments, organizational support systems, and individual agencies in bridging the gap between training participation and pedagogical transformation.